Value of blood pressure measurement earlier versus later in life to predict cardiovascular mortality. (3rd October 2022) - Leiherer, A; Ulmer, H; Muendlein, A; Saely, C H; Fraunberger, P; Mader, A; Sprenger, L; Maechler, M; Vonbank, A; Larcher, B; Brozek, W; Nagel, G; et al.
Abstract: : Hypertension is a potent risk factor for cardiovascular morbidity and mortality. High blood pressure (BP) correlates closely with all-cause and cardiovascular mortality. The purpose of this study was to compare the value of systolic blood pressure earlier versus later in life to predict cardiovascular mortality. In a cardiovascular observation study (OS) we prospectively recorded fatal cardiovascular events over up to 19 years in 1282 patients of whom 570 had the Metabolic Syndrome (MetS) at baseline. These patients had participated in a health survey (HS) 15 years prior to the OS baseline. BP was measured both at the HS and at the baseline of the OS. We found that the increase in cardiovascular mortality matched the increase of BP in the HS in a linear way but this is not the case for BP assessed at the OS (figure). A cox regression analysis revealed that each millimeter of mercury (mm Hg) increased the risk for cardiovascular death by 2% (HR = 1.02 [1.01–1.03], p<0.001). Applying a stratification for the presence of MetS, we found that in both groups BP was a significant predictor of cardiovascular mortality (HRMetS = 1.02 [1.01–1.02], p<0.001 and HRnoMetS = 1.02 [1.01–1.03], p<0.001). In contrast, BP as measured at the baseline of the OS was not significantly associated with cardiovascular death during follow-up neither in the total population nor in any subgroup (HR = 1.00 [0.99–1.01], p=0.652; HRMetS = 1.00 [0.99–1.01], p=0.468 and HRnoMetS = 1.00 [0.99–1.01], p=4.66). We thus conclude that BP assessed earlier in life is a better predictor of cardiovascular mortality than BP assessed later in life. Funding Acknowledgement: Type of funding sources: None.